Autonomic Modulation in Resistance-Trained Individuals after Acute Resistance Exercise - Kingsley, J. D.; Hochgesang, S.; Brewer, A.; Buxton, E.; Martinson, M.; Heidner, G. (International Journal of Sports Medicine, 2014)
The effects of different types of acute bouts of resistance exercise on autonomic modulation in individuals that are resistance-trained compared to untrained individuals are unknown. Seventeen untrained and 17 resistance-trained participants were assessed for autonomic modulation after various acute resistance exercise bouts. Electrocardiogram readings were collected at rest and 25 min after a control period, whole-, lower-, or upper-body acute bouts of resistance exercise. Heart rate variability and heart rate complexity were used to assess autonomic modulation. Participants were similar for age, height, weight and measures of body composition (p>0.05) and were different for measures of maximal strength (p<0.05). There were no differences (p>0.05) in autonomic modulation at rest between groups. Significant decreases (p<0.05) in parasympathetic modulation after the acute bouts of resistance exercise were noted. Sample entropy was not affected in the untrained group, but was significantly decreased after whole- (−17.5%) and upper-body exercise (−13.5%) in the resistance training group. The changes in sample entropy after lower-body resistance exercise were not significant (−15.7%; p=0.06). These data suggest that resistance exercise training further attenuates the parasympathetic responses to an acute bout of resistance training regardless of the modality compared to the untrained state.
Keywords: strength training; spectral analysis; sample entropy